Detection of Land Cover Change in Nickel Mining Areas, in Weda Tengah Sub-district, Halmahera Island, Indonesia using Planet-Scope Satellite Images - Rakuasa, Heinrich; Ahmat Rifai , Ahmat Rifai; Latulanit , Abdul Kadir; Amahoru , Abd H; Laitupa , Rizky Ahmad; Diaz Astiza , Diaz Astiza; Rajani , La Mbeli (CV. Science Tech Group, 2025)
Land cover change is a global phenomenon triggered by human activities, including mining, which has significant impacts on the environment and ecosystems. In Indonesia, particularly on Halmahera Island, nickel mining has become one of the main economic sectors, but this activity often results in serious environmental degradation. The data used in this study is PlanetScope satellite image data for 2016, 2020 and 2024 which has a 3-meter spatial resolution. The image data was then interpreted and digitized to obtain land cover classes consisting of settlements, farming areas, vegetation and water bodies. The validation results of land cover in 2016, 2020, and 2024 obtained accuracy values of 92%, 90%, and 95%, respectively. In 2016, settlements had an area of 222.79 ha, mining area of 364.98 ha, vegetation of 52,938.88 ha, water body of 212.88 ha. In 2020, settlements were 343.92 ha, mining areas were 1,329.18 ha, vegetation was 51,853.55 ha, water bodies were 212.88 ha. In 2024, settlements are 563.92 ha, mining area is 4,498.32 ha, vegetation is 48,464.41 ha and water bodies are 212.88 ha. The mining area certainly continues to increase in area every year.